Optimum community energy storage system for demand load shifting - Parra, David; Norman, Stuart A.; Walker, Gavin S.; Gillott, Mark (Elsevier, 2016)
Community energy storage (CES) is becoming an attractive technological option to facilitate the use of distributed renewable energy generation, manage demand loads and decarbonise the residential sector. There is strong interest in understanding the techno-economic benefits of using CES systems, which energy storage technology is more suitable and the optimum CES size. In this study, the performance including equivalent full cycles and round trip efficiency of lead-acid (PbA) and lithium-ion (Li-ion) batteries performing demand load shifting are quantified as a function of the size of the community using simulation-based optimisation. Two different retail tariffs are compared: a time-of-use tariff (Economy 7) and a real-time-pricing tariff including four periods based on the electricity prices on the wholesale market. Additionally, the economic benefits are quantified when projected to two different years: 2020 and a hypothetical zero carbon year.